A cluster randomized controlled trial of a MedicineInsight Educational Quality Improvement Programme to improve the diagnosis and treatment of chronic hepatitis C in general practice (the EQUIP‐HEPC trial). Issue 2 (16th November 2021) - Chidwick, Kendal; Myton, Rimma; Rodgers, Anthony; Jun, Min; Dartnell, Jonathan; Balcomb, Annie; Dore, Gregory
Abstract: The availability of direct‐acting antivirals (DAAs) sparked efforts to eliminate hepatitis C virus (HCV) in Australia. We evaluated whether an educational intervention of a 1‐h discussion among staff using audit and feedback data from the MedicineInsight GP programme would improve DAA uptake. Of 296 eligible general practices in MedicineInsight, 11% opted out. Randomization stratified by practice caseload allocated 130 practices to the intervention arm and 129 to control. The primary outcome was the number of patients started on DAAs over 6 months using the negative binomial regression model adjusted for DAA prescription history and clustering by practice. Data for analysis were available for 78% of practices, which included 101 practices and 2469 DAA‐naive patients with confirmed/possible HCV in the intervention arm, and 100 practices and 2466 patients in the control arm. At baseline, 49.5% of practices had prescribed ≥1 DAA in the past year; 18.9% of HCV patients had already been treated with DAAs; the mean age of DAA‐naive HCV patients was 43 years old, and 57% were men. Over 6 months, 43 patients in the intervention arm and 36 in the control arm started DAAs (adjusted IRR 1.19; 95% CI 0.67–2.11, p  = 0.55). In the first 3 months, 27 vs 16 patients started DAAs (adjusted IRR 1.77, 0.88–3.58; p  = 0.111). Few patients were started on DAAs, and a facilitated discussion in HCV management did not lead to a significant increase. Alternative measures, such as incentivizing GP initiations or patients, are suggested to address remaining barriers to DAA uptake in Australian primary care. Australian New Zealand Clinical Trial Registry (ANZCTR) Registration Number: ACTRN12619000508178p.